2019
DOI: 10.3389/fmars.2019.00397
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Suspension-Feeding and Flux-Feeding Zooplankton as Gatekeepers of Particle Flux Into the Mesopelagic Ocean in the Northeast Pacific

Abstract: Zooplankton are important consumers of sinking particles in the ocean's twilight zone. However, the impact of different taxa depends on their feeding mode. In contrast to typical suspension-feeding zooplankton, flux-feeding taxa preferentially consume rapidly sinking particles that would otherwise penetrate into the deep ocean. To quantify the potential impact of two flux-feeding zooplankton taxa [Aulosphaeridae (Rhizaria), and Limacina helicina (euthecosome pteropod)] and the total suspensionfeeding zooplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 128 publications
(177 reference statements)
3
44
0
Order By: Relevance
“…There are many potential possibilities for explaining such discrepancies. As hypothesized by Jackson and Checkley (2011), zooplankton may play an important role at this depth, particularly if they are suspension-feeders with high clearance rates that remove most of the slowly sinking particles before they reach deeper depths (Stukel et al, 2019b). Sinking rates of low excess density marine snow may also be retarded at density gradients found near the base of the mixed layer (Macintyre et al, 1995;Prairie et al, 2015).…”
Section: Vertical Particle Flux and Attenuationmentioning
confidence: 93%
See 1 more Smart Citation
“…There are many potential possibilities for explaining such discrepancies. As hypothesized by Jackson and Checkley (2011), zooplankton may play an important role at this depth, particularly if they are suspension-feeders with high clearance rates that remove most of the slowly sinking particles before they reach deeper depths (Stukel et al, 2019b). Sinking rates of low excess density marine snow may also be retarded at density gradients found near the base of the mixed layer (Macintyre et al, 1995;Prairie et al, 2015).…”
Section: Vertical Particle Flux and Attenuationmentioning
confidence: 93%
“…Throughout the manuscript we are careful to differentiate between direct POC flux estimates made by sediment traps and blended POC flux estimates determined as above. For more details on calculating these blended profiles see Stukel et al (2019b).…”
Section: Blended Flux Attenuationmentioning
confidence: 99%
“…In icecovered regions, the phytoplankton community is strongly influenced by water stratification due to ice melt, while more porous ice conditions during summer could have triggered the release and vertical export of ice algal material, thus contributing to the PPOM community composition (Hegseth, 1998;Tamelander et al, 2009). Limacina helicina is described as a flux-feeder with the ability to consume fast-sinking food particles (Stukel et al, 2019), such as ice algal aggregates dominated by pennate diatoms (Assmy et al, 2013), which have been shown to contain HBI-producing diatoms albeit in low abundances (Brown et al, 2017a), providing an explanation for the highest concentrations of sea ice algae-associated HBIs in L. helicina in this study. The absence of sea ice algaeassociated HBIs does not exclude the possibility of the other taxa to feed on sea ice-derived carbon.…”
Section: Pteropods and Gelatinous Zooplanktonmentioning
confidence: 99%
“…Although sinking particles can efficiently support bacterial production (as they are likely directly colonized by particle-attached bacteria), many fish and gelatinous zooplankton are predators that more likely feed on living organisms than on the sinking fecal pellets that typically dominate particle flux in the CCE. For these planktivorous organisms, sustaining their metabolism through a food chain supported by sinking particles would likely require one (if not more) trophic levels to separate them from the export source, depending on whether the sinking particles are consumed by filter- or flux-feeding zooplankton or by microbes (Stukel et al, this issue). Thus, sustaining the high carbon demand of mesopelagic myctophids with sinking particles requires substantially more total carbon flux than does sustaining it via active transport of the myctophids’ prey.…”
Section: Discussionmentioning
confidence: 99%
“…Within the mesopelagic, zooplankton also play an important biogeochemical role in the attenuation of particle flux (Buesseler and Boyd, 2009; Steinberg et al, 2008; Stukel et al, this issue) and in effecting elemental cycling (Kiko et al, this issue; Robinson et al, 2010). Our results suggest that mesozooplankton detritivory accounted for the consumption of 57% - 71% of sinking particles from the epipelagic, with bacterially-mediated remineralization of the majority of the remainder (i.e.…”
Section: Discussionmentioning
confidence: 99%